ZNS SSD의 수명 향상을 위한 스페어 존 기법 - 이찬용(Chanyong Lee); 강동현(Donghyun Kang) (정보과학회 컴퓨팅의 실제 논문지, 2024)
최근 주목받는 ZNS SSD는 SSD의 주소공간을 동일한 크기의 존(Zone) 단위로 구분하고 존 리셋(Zone reset)을 통해 존 단위로 데이터를 초기화한다. 이때 존의 사용하지 않는 블록까지 초기화하며 초기화 횟수가 제한된 블록의 수명을 낭비하는 문제가 발생한다. 본 논문에서는 존 리셋으로 인한 ZNS SSD의 수명 낭비 문제를 해결하기 위해 존의 남은 공간이 있는 경우, 존 리셋을 지연시키고 남은 공간을 재사용하는 스페어 존 기법을 제안한다. 우리는 제안 기법을 구현하기 위해 NVMeVirt의 일부 코드를 수정하였다. 또한, ZNS SSD의 수명 향상을 평가하기 위해 F2FS 환경에서 YCSB 워크로드를 이용하여 기존의 ZNS SSD와 비교하였다. 실험 결과, 리얼 워크로드에서 존 리셋의 총 수행 횟수가 최대 54% 감소하였고, 성능은 최대 6% 증가함을 확인하였다. Recently, ZNS SSDs have garnered attention for dividing SSD address space into zones of equal size and resetting data on a zone basis through zone reset. However, this process also resets unused blocks within the zone, leading to wastage of block lifetime, which has a limited number of reset cycles. This paper proposes a spare zone technique that can delay zone reset and reuse the remaining space in the zone when there is unused space, to address the problem of lifetime wastage in ZNS SSDs caused by zone reset. We modified portions of NVMeVirt's code to implement the proposed technique. To evaluate improvement in ZNS SSD lifetime using the proposed technique, we compared it with existing ZNS SSDs using fio and YCSB in an F2FS environment. Experimental results showed that the total number of zone resets decreased by up to 54% in real workloads whereas performance increased by up to 6%. KCI Citation Count: 0